Melanin characterisation suggests that the “brown” phenotype in alpaca (Vicugna pacos) is predominantly pheomelanic - Cransberg, Rhys; Wakamatsu, Kazu; Munyard, Kylie (Elsevier BV, 2013)
The “brown” phenotype in alpacas, as described by breeders, is heterogeneous and probably has diverse aetiology. Various “brown” alpaca phenotypes were investigated to try to determine their genetic origin. Using both spectrophotometric and HPLC tests we have determined the total amount of melanin and relative amounts of eumelanin and pheomelanin in a group of alpacas from Australia. The distribution of colour across different parts of the fleece was also analysed. Spectrophotometrically there was no significant difference in the eumelanin:pheomelanin ratio between white and light fawn (P = 0.238), fawn(P = 0.428), brown (P = 0.208), and red brown samples (P = 0.232); all of which were predominantly pheomelanic. This data was supported by a comparison between alpacas described as “brown” by breeders, and known eumelanic brown dogs, between which a clear difference in the type of melanins present was seen. HPLC analysis confirmed that the fibre of all the “brown” alpacas sampled in this study contained predominantly pheomelanic melanin, rather than eumelanin, indicating the possible absence of the eumelanic brown phenotype in the species. This data suggests that “brown” in alpacas is predominantly caused by pheomelanin and that variations between different “brown” colours are caused by changes in pheomelanin levels, and relative amounts of black eumelanin, as opposed to brown eumelanin.